Two new species of the genus Plusiodonta Guenée, 1852 from Southeast Asia (Lepidoptera, Erebidae: Calpinae) - Behounek, G.; Kononenko, V. S.; Pellinen, M.j. (Zootaxa, 2017)
Two new species of the genus Plusiodonta Guenée, 1852, Plusiodonta pasi sp. n. and Plusiodonta stumpfi sp. n. are described from Thailand and Philippines. The distribution of Plusiodonta calcaurea Holloway, 2005 in Southeast Asia is clarified. The adult and genitalia of referred species as well as male and female of Plusiodonta coenolota (Kollar, 1844) are illustrated. The checklist the genus Plusiodonta over the World is presented.